Application of computational methods in elucidating the isomerization step in the biosynthesis of coumarins - Tshiwawa, Tendamudzimu (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
The identity of the enzyme(s) responsible for the biosynthetic transformation of cinnamic acid derivatives to important, naturally occurring coumarins has yet to be established. This study constitutes a high-level theoretical analysis of the possibility that a recently reported molecular mechanism of the synthesis of coumarins from Baylis-Hillman adducts, may provide a viable model for three critical phases in the biosynthetic pathway Particular attention has been given to the first of these phases: i) Eâ†’Z isomerisation of the cinnamic acid precursor; ii) Cyclisation (lactonisation) to the hemi-acetal intermediate; and ii) Dehydration to afford the coumarin derivative. In order to accomplish this analysis, an enzyme capable, theoretically, of effecting this Eâ†’Z isomerisation required identification, and its potential involvement in the transformation mechanism explored. Combined Molecular Mechanics and high-level Quantum Mechanical/DFT calculations were used to access complementary models of appropriate complexes and relevant processes within the enzyme active sites of a range of eleven Chalcone Isomerase (CHI) enzyme candidates, the structures of which were downloaded from the Protein Data Bank. Detailed B3LYP/6-31+G(d,p) calculations have provided pictures of the relative populations of conformations within the ensemble of conformations available at normal temperatures. Conformations of several protonation states of cinnamic acid derivatives have been studied in this way, and the results obtained showed that coupled protonation and deprotonation of (E)-o-coumaric acid provides a viable approach to achieve the Eâ†’Z isomerization. In silico docking of the B3LYP/6-31+G(d,p) optimized (E)-o-coumaric acid derivatives in the active sites of each of the candidate CHI enzymes (CHI) revealed that (E)-o-coumaric acid fits well within the active sites of Medicago Sativa CHI crystallographic structures with 1FM8 showing best potential for not only accommodating (E)-o-coumaric acid , but also providing appropriate protein active site residues to effect the simultaneous protonation and deprotonation of the substrate , two residues being optimally placed to facilitate these critical processes. Further exploration of the chemical properties and qualities of selected CHI enzymes, undertaken using High Throughput Virtual Screening (HTVS), confirmed 1FM8 as a viable choice for further studies of the enzyme-catalysed Eâ†’Z isomerization of (E)-o-coumaric acid. A molecular dynamics study, performed to further evaluate the evolution of (E)-o-coumaric acid in the CHI active site over time, showed that the ligand in the 1FM8 active site is not only stable, but also that the desired protein-ligand interactions persist throughout the simulation period to facilitate the Eâ†’Z isomerization. An integrated molecular orbital and molecular mechanics (ONIOM) study of the 1FM8-(E)-o-coumaric acid complex, involving the direct protonation and deprotonation of the ligand by protein residues; has provided a plausible mechanism for the E â†’ Z isomerization of (E)-o-coumaric acid within the 1FM8 active site; a transition state complex (with an activation energy of ca. 50 kCal.mol-1) has been located and its connection with both the (E)- and (Z)-o-coumaric acid isomer has been confirmed by Intrinsic Reaction Coordinate (IRC) calculations. More realistic models of the 1FM8-(E)-o-coumaric acid complex, with the inclusion of water solvent molecules, have been obtained at both the QM/MM and adaptive QM/MM levels which simulate the dynamic active site at the QM level. The results indicate that the simultaneous protonation and deprotonation of (E)-o-coumaric acid within the CHI enzyme is a water-mediated process "“ a conclusion consistent with similar reported processes. Visual inspection of the 1FM8-(Z)-o-coumaric acid complex reveals both the necessary orientation of the phenolic and carboxylic acid moieties of the (Z)-o-coumaric acid and the presence of appropriate, proximal active site residues with the potential to permit catalysis of the subsequent lactonisation and dehydration steps required to generate coumarin.
Keywords: Coumarins; Isomerization; Biosynthesis; Organic compounds -- Synthesis; Cinnamic acid